Participant Reactions to a Literacy-Focused, Web-Based Informed Consent Approach for a Genomic Implementation Study. Issue 1 (26th September 2020) - Kraft, Stephanie A.; Porter, Kathryn M.; Duenas, Devan M.; Guerra, Claudia; Joseph, Galen; Lee, Sandra Soo-Jin; Shipman, Kelly J.; Allen, Jake; Eubanks, Donna; Kauffman, Tia L.; Lindberg, Nangel M.; Anderson, Katherine; et al.
Abstract: Background: Clinical genomic implementation studies pose challenges for informed consent. Consent forms often include complex language and concepts, which can be a barrier to diverse enrollment, and these studies often blur traditional research-clinical boundaries. There is a move toward self-directed, web-based research enrollment, but more evidence is needed about how these enrollment approaches work in practice. In this study, we developed and evaluated a literacy-focused, web-based consent approach to support enrollment of diverse participants in an ongoing clinical genomic implementation study. Methods : As part of the Cancer Health Assessments Reaching Many (CHARM) study, we developed a web-based consent approach that featured plain language, multimedia, and separate descriptions of clinical care and research activities. CHARM offered clinical exome sequencing to individuals at high risk of hereditary cancer. We interviewed CHARM participants about their reactions to the consent approach. We audio recorded, transcribed, and coded interviews using a deductively and inductively derived codebook. We reviewed coded excerpts as a team to identify overarching themes. Results : We conducted 32 interviews, including 12 (38%) in Spanish. Most (69%) enrolled without assistance from study staff, usually on a mobile phone. Those who completed enrollment in one day spent an average of 12 minutes on the consent portion. Interviewees found the information simple to read but comprehensive, were neutral to positive about the multimedia support, and identified increased access to testing in the study as the key difference from clinical care. Conclusions : This study showed that interviewees found our literacy-focused, web-based consent approach acceptable; did not distinguish the consent materials from other online study processes; and valued getting access to testing in the study. Overall, conducting empirical bioethics research in an ongoing clinical trial was useful to demonstrate the acceptability of our novel consent approach but posed practical challenges.